Association between metabolic syndrome and left ventricular geometric change including diastolic dysfunction - Lee, Seung‐Jae; Kim, Hyunah; Oh, Byeong Kil; Choi, Hyo‐In; Sung, Ki‐Chul; Kang, Jeonggyu; Lee, Mi Yeon; Lee, Jong‐Young (Clinical cardiology (Mahwah, N.J.), 2022)
Background We investigated the association between individual components of metabolic syndrome (MetS) and left ventricular (LV) geometric changes, including diastolic dysfunction, in a large cohort of healthy individuals. Methods Overall, 148 461 adults who underwent echocardiography during a health‐screening program were enrolled. Geographic characteristics on echocardiography and several markers of LV relaxation function were identified according to individual MetS components. Univariate linear regression analysis and a multivariate regression model adjusted for factors known to influence LV relaxation function were conducted. Results The prevalence of LV diastolic dysfunction (LVDD) was higher in the MetS group than in the non‐MetS group (0.56% vs. 0.27%, p < .001). In univariate and multivariate analyses, E/A ratio, e′ velocity, and left atrial volume index were significantly associated with each component of MetS and covariates (all p ≤ .001). In the age‐ and sex‐adjusted model, MetS was significantly associated with LVDD (odds ratio [95% confidence interval], 1.350 [1.103, 1.652]). However, subjects with more MetS components did not have a significantly higher risk of LVDD. As the analysis was stratified by sex, the multivariate regression model showed that MetS was significantly associated with LVDD only in men (1.3 [1.00, 1.68]) with higher risk in more MetS component (p for trend < .001). In particular, triglyceride (TG) and waist circumference (WC) among MetS components were significantly associated with LVDD in men. Conclusions MetS was associated with the risk of LVDD, especially in men, with a dose‐dependent association between an increasing number of components of MetS and LVDD. TG and WC were independent risk factors for LVDD in men.